Complaint Responses Used By Indonesian Efl Learners - Sulastri., Endang; , Agus Wijayanto, Ph.D; , Siti Zurhriah Ariatmi, M. Hum (2014)
This research aims to describe the use of complaint responses strategies, the use of politeness strategies in complaint responses and different gender induce the use of complaint responses strategy by Indonesian EFL learners in Muhammadiyah University of Surakarta. The study uses descriptive qualitative research in which the research participants were forty Indonesian EFL learners at seventh semester at English education department, Muhammadiyah University of Surakarta. The data were spoken utterances of complaint response strategies elicited through oral DCT (Discourse Completion Tasks) scenarios. The subject consists of twenty male and twenty female participants. The data of complaint responses strategy were analyzed by code schema in Eslami and Rasekh (2004) also added by Brown and Levinson (1987) theory as the type of politeness strategy. The research findings showed that Indonesian EFL learners' strategies of complaint responses have tendency of IFIDs 4.4% (based on DCT 8), of explanation or account 5.8% (based on DCT 6), of acceptance responsibility 2.9% (based on DCT 2), of expression of appeal 2.1% (based on DCT 3), of refusing responsibility 2.4% (based on DCT 4), of concern to the hearer (based on DCT 6), of offer of repair 2.1% (based on DCT 1), of promise of forbearance 0.8% (based on DCT 2) and emotional exclamation 2.1% (based on DCT 4 and DCT 7). As for politeness, Indonesian EFL learners have tendency of PP 5.3% (based on DCT 1), of PP 5.8% (based on DCT 2), of PP 1 7.9% (based on DCT 3), of NP 5.3% (based on DCT 4), of PP 5.4% (based on DCT 5), of PP 6.3% (based on DCT 6), of PP 5.8% (based on DCT 7), of NP 5.6 % (based on DCT 8) and of NP 4.7% (based on DCT 9). In the last as different genders of Indonesian EFL learners induce different use of complaint response strategies have tendency of explanation or account (female 13.3%, male 10.8%), emotional exclamation (female 4.2%, male 5.0%), of offer of repair (female 6.0%, male 5.7%), concern to the hearer (female 0.7%, male 1.1%), of refusing responsibility (female 2.8%, male 3.8%), of expression of appeal (female 5.0%, male 4.6%), of acceptance responsibility (female 6.0%, male 6.3%) and of IFIDs (female 11.0%, male 12.5%).